Application of machine learning based on habitat imaging and vision transformer to predict treatment response of locally advanced esophageal squamous cell carcinoma following neoadjuvant chemoimmunotherapy: a multi-center study - Xie, Shu-Han; Xu, Hui; Zhang, Hai; Xu, Jin-Xin; Huang, Shi-Jie; Liu, Wen-Yi; Tang, Zi-Lu; Xu, Rong-Yu; Ke, Sun-Kui; Xie, Jin-Biao; Feng, Qing-Yi; Kang, Ming-Qiang (Frontiers in Immunology, 2025)
ObjectiveCurrent medical examinations and biomarkers struggle to assess the efficacy of chemoimmunotherapy (nICT) for locally advanced esophageal squamous cell carcinoma (ESCC). This study aimed to develop a machine learning model integrating habitat imaging and deep learning (DL) to predict the treatment response of ESCC patients to nICT.MethodsThe study retrospectively collected 309 ESCC patients from 6 medical centers, divided into training and external validation cohorts. For habitat imaging analysis, intratumoral subregions were clustered using the K-means clustering method. DL features from intratumoral and peritumoral subregions were extracted by Vision Transformer (ViT) respectively and then subjected to feature selection. Subsequently, 11 machine learning models were constructed for predictive model. The model’s performance was evaluated using the area under the curve (AUC), decision curve analysis (DCA), calibration curve, and accuracy.ResultsA total of 18 DL features were selected. The model of ExtraTrees, which was optimal, demonstrated superior performance with AUCs of 0.917 in training cohort and 0.831 in external validation cohort. Similarly, ExtraTrees showed good predictive capabilities in patients undergoing 2 cycles of nICT with AUC of 0.862 in validation cohort. This model also showed good calibration for prediction probability and satisfied clinical value on DCAs. Finally, the SHapley Additive exPlanations method elucidated the model’s precise predictions.ConclusionThe ExtraTrees model leveraging habitat imaging and ViT offered a non-invasive and accurate method to predict pathological response to nICT, guiding personalized treatment strategies, and decreasing the risk of immune-related adverse effects.